WasTic: future soil stabilizer / Nor Hafizah Hanis Abdullah ... [et al.] - Abdullah, Nor Hafizah Hanis; Keria, Roziah; Musir, Adhilla Ainun; Abdul Karim, Nurulzatushima; Rosseli, Siti Rahimah (2020)
Problems of excessive settlement due to consolidation process in compressible soil is inevitable at some construction sites in Malaysia. For earthworks, soil with good bearing capacity and strength is required to support the structural loads. Sometimes, locally available soil is not eligible for construction works. Soil stabilization method is needed to make sure the stability and control of soil settlement of the embankment. Hence, WasTic has been innovated to fulfill the requirement as soil stabilizer compliance. WasTic comprises of waste plastic as the main reinforcement agent for the soil. Several series of experimental works have been carried out to investigate the potential of waste plastic to stabilize the soil consolidation behavior by using Unconfined Compression Test (UCT). WasTic is mixed and compacted with the soil samples at different moisture content. Each moisture level is mixed with different percentage of the plastic waste. Results showed that the required amount of plastic waste is 1.5 % in order to be increase the shear strength of the soil. Utilisation of WasTic as soil stabilizer promotes environmentally friendly approach to the construction industry, thus helps in creating a sustainable development in the scope of civil engineering practices.